(3JMaI GdGfaS hTYGQ Cgd GdGfOdSs - (3Ydj Hf YHO GdQMef Hf gPjd GdaRGQj GdCfOdSj,J (B763 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefYe HShGHZ Gdeff hGdBdGA CeG HYO cJH Gddg GdfUQ GdeDjO s
(3BNQgG (B:s
(3GdacQI JUdM GdQCI bHd GdJeGe GdMQH hJajjOg HYO GfJgi s
(3HgG fXGe GdJYbjHIs
(3dYdg GdeNWhW cJGH MdjI GdaQSGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B121s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs